Investigating different factors for regional market entrance - Ali Ghasemi; Abohamid Hajipour Shooshtari (Management Science Letters)
This paper presents an empirical investigation to study the effects of different factors for regional market entrance. The population of this survey includes all producers who are involved in export of industrial goods in city of Tehran, Iran. The study designs a questionnaire in Likert scale and distributes it among some randomly selected experts who were involved in production and export of different products. Cronbach alpha was calculated as 0.856, which is well above the minimum acceptable level. Using principal component analysis, the study has detected seven factors including product development, government support, strategic orientation, customer satisfaction, competitive pressure, organizational capabilities and distribution strategies influencing on product development. In addition, the implementation of structural equation modeling has determined that product development, government support, strategic orientation and competitive pressure maintained the highest effects on product development.